Using a Criminally Involved Population to Examine the Relationship Between Race/Ethnicity, Structural Disadvantage, and Methamphetamine Use - Fox, Andrew M. (Crime & delinquency, 2014)
Limited empirical focus has been given to identifying individual and structural correlates of methamphetamine use. Although race (i.e., being White) is one of the most distinguishing characteristics of methamphetamine users, few studies have examined whether race/ethnicity is a significant predictor of such illicit drug use. Research has also shown that cocaine and opiate use is associated with disadvantage; however, studies have yet to examine the relationship between structural disadvantage and methamphetamine use. Using national data from the Arrestee Drug Abuse Monitoring program, this study examines the prevalence of methamphetamine and explores the relationship between race/ethnicity, structural disadvantage, and methamphetamine use. Findings reveal that race/ethnicity and structural disadvantage are significant predictors of methamphetamine use. Additionally, findings show an interactive effect between race/ethnicity, structural disadvantage, and methamphetamine use. Implications for policy and practice are discussed.